STRATEGI PENGEMBANGAN PERGURUAN TINGGI (PTS) DI INDONESIA DALAM MENGHADAPI ERA PERUBAHAN - Paradita Gea Brillikatrin; Muhammad Ramaditya (UNIVERSITAS KARIMUN, 2023)
This study aims to identify how private universities in Indonesia survive and develop and identify development strategies used by private universities in Indonesia in facing the era of change. This study uses a descriptive qualitative approach with a literature review research design and historical analysis methods. The data is sourced from news and journals, a total of 340 data sources and obtained from online publications through trusted sites and indexes. The results of this study are in the form of a strategy typology that can provide a broader view for private universities if they want to develop their institutions according to the resources they have. Developments in educational institutions can be in the form of restructuring, exploring new markets, establishing cooperation or networking with external parties, participating in private higher education development programs, developing human resources in private universities, especially educators and education staff, as well as university social responsibility.